2020
DOI: 10.4049/jimmunol.2000101
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycan Branching Is Required for Development of Mature B Cells

Abstract: Galectins have been implicated in inhibiting BCR signaling in mature B cells but promoting pre-BCR signaling during early development. Galectins bind to branched N-glycans attached to cell surface glycoproteins to control the distribution, clustering, endocytosis, and signaling of surface glycoproteins. During T cell development, N-glycan branching is required for positive selection of thymocytes, inhibiting both death by neglect and negative selection via enhanced surface retention of the CD4/CD8 coreceptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…However, the dramatic reduction in BCR and CD19 surface expression induced by Mgat1 (but not Mgat2) deficiency is dominant, thereby reducing BCR signaling despite a potential decrease in galectin-9 binding to BCR. Consistent with this, we recently observed that deleting Mgat1 in pro/pre-bone-marrow B cells completely blocks development of mature B cells by reducing CD19/BCR signaling (Mortales et al, 2020).…”
Section: Ll Open Access Isciencesupporting
confidence: 80%
See 1 more Smart Citation
“…However, the dramatic reduction in BCR and CD19 surface expression induced by Mgat1 (but not Mgat2) deficiency is dominant, thereby reducing BCR signaling despite a potential decrease in galectin-9 binding to BCR. Consistent with this, we recently observed that deleting Mgat1 in pro/pre-bone-marrow B cells completely blocks development of mature B cells by reducing CD19/BCR signaling (Mortales et al, 2020).…”
Section: Ll Open Access Isciencesupporting
confidence: 80%
“…Mgat1 deficiency is expected to produce a more severe phenotype than Mgat2 deficiency, as the former eliminates, whereas the latter only reduces branching ( Figure S1 A) ( Mkhikian et al, 2016 ; Zhou et al., 2014 ). Indeed, whereas CD19-driven cre-deletion of Mgat2 had no impact on B cell development, deletion of Mgat1 completely blocked B cell development ( Mortales et al., 2020 ). Therefore, to examine Mgat1 deficiency in mature peripheral B cells, we utilized Mgat1 f/f /tetO-cre/ROSA-rtTA mice ( Zhou et al., 2014 ), where doxycycline consistently induces Mgat1 deficiency in ∼35%–40% of mature ex vivo splenic B cells.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, α2-6 sialic acid is absent in pSS B cells and barely present in SLE, whereas α-fucose is reduced only in SLE B cells. In-depth characterisations have revealed that memory B cells are remarkably altered, and these glycosylation changes could explain the positive selection of autoreactive B cells ( 49 , 53 ), and the increased activation of BCR caused by the absence of CD22 sialic acid ligands ( 39 , 52 , 54 ). In contrast to pSS B cells, SLE B cells exhibit Gal-GlcNAc/Gal-GalNAc terminal patterns, suggesting a lack of terminal glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…N-glycosylation is one of the most important post-translational protein modifications 1 . N-glycans are involved in various biological phenomena such as development 1 3 , pluripotency 4 6 , differentiation 5 8 , regeneration 9 , 10 , and carcinogenesis 11 , 12 . In the neural system, N-glycans play crucial roles in neuronal system development 13 , 14 , neuroplasticity 14 , 15 , differentiation 7 , 14 , the regulation of signal transduction 13 , and are involved in the onset of neurodegenerative diseases 16 .…”
Section: Introductionmentioning
confidence: 99%